Records of St. Peter's Parish, New Kent County, Va. - St. Peter's Parish (New Kent County, Va.)
Fragments of financial records of the parish.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Church of England -- Virginia -- History -- 18th century; Episcopal Church -- Virginia -- History -- 18th century; New Kent County (Va.) -- History; Virginia -- Church history -- 18th century